The Lexical Basis of Second Language Reading Comprehension: From (Sub)Lexical Knowledge to Processing Efficiency. Issue 2 (9th December 2021) - Alshehri, Mona G.; Zhang, Dongbo
Abstract: This study compared how distinct lexical competences, including lexical knowledge as well as processing skills at both word/lexical and sublexical/morphological levels, collectively and relatively predict reading comprehension in adult learners of English as a foreign language (EFL). The participants were 220 Arabic‐speaking EFL learners in a Saudi university. A battery of paper‐ and computer‐based tests was administered to measure the participants' lexical competences, reading comprehension ability, and working memory. Hierarchical regression analyses revealed that over and above working memory, both lexical and sublexical knowledge were significant and unique predictors of reading comprehension, and sublexical processing efficiency, as opposed to lexical processing efficiency, predicted reading comprehension significantly. In addition, among the measured lexical competences, lexical knowledge was the strongest predictor, and the two knowledge variables collectively had a far greater influence on reading comprehension than did the two processing efficiency variables. These findings are discussed in light of the lexical basis of text comprehension. Abstract :